EFFICIENT SEPARATION OF FIBERS FROM SAW TEETH IN THE NEWLY DESIGNED GIN MACHINE - Mirzakarimov, Mirsharoffiddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article examines several models of the device for efficient air separation of fibers from a gin machine's saw teeth, analyzes them both theoretically and practically, tests the suggested device for efficient air separation of fibers from a gin machine's saw teeth, and develops a new design based on the findings. A simulation of the new design is carried out following the identification of the effective parameters for enhancing the air separation of fibers from a gin machine's saw teeth.